RELIABILITY ANALYSIS OF THE LIQUID TARGET CHAMBER FOR 18F PRODUCTION AT THE PRR'S CYCLOTRON FACILITIES - Kambali, Imam; Sumantri, Tonny Heryanto; Rajiman, Rajiman; Ichwan, Syaefudin (Jurnal Radioisotop dan Radiofarmaka, 2009)
ABSTRACT RELIABILITY ANALYSIS OF THE LIQUID TARGET CHAMBER FOR 18F PRODUCTION AT THE PRR'S CYCLOTRON FACILITIES. The liquid target chamber for 18F production at the Cyclotron Division, Centre for Radioisotopes and Radio- pharma ceuticals (PRR) of themÂ Indonesian National Nuclear Energy Agency (BA TAN) has been analysed for its reliability in enduring high pressures and heat transfer requirements during proton beam bombardment as well as the recommended irradiation parameters for effective 18Fproduction. The target chamber was subject to house the 180-enriched water bombarded with high energy proton beam to produce 18F.A range of SRIM-computer simulations have also been conducted to calculate the ranges of several energetic proton beams (of up to 20 MeV) into pure water target. A study of radioactive impurities which might be produced from the proton-irradiated chamber's materials was also included based on some references. Due to concern over the heat produced during target irradiation, a heat transfer analysis - particularly for the target's cavity - was also included in the presented studies to obtain a brief preliminary calculation of the heating impacts prior to irradiation tests. The calculation was performed for various proton beam currents and energies of up to 30 J..lAand 20 MeV. respectively. It was found that the chamber was reliable for production of 18Ffrom proton irradiated-180 enriched-water target by maintaining the chamber's pressure of up to 3.6 bar if the proton beam current was kept below 16 J..lAfor all energies or the proton beam energy was kept to or below 10 MeV for any employed beam currents. The overall heat transfer coefficient was also found to depend on the power deposited into the water target. Keywords: reliability analysis, liquid target chamber, 18F production, proton irradiation, cyclotron, 180_enriched water target, heat transfer coefficient. ABSTRAK ANALISIS KEHANDALAN CHAMBER TARGET CAIR UNTUK PRODUKSI 18F DI FASILITAS SIKLOTRON PRR. Telah dilakukan analisis kehandalan terhadap chamber target cair untuk produksi 18F yang dimiliki oleh Bidang Siklotron, Pusat Radioisotop dan Radiofarmaka (PRR), Badan Tenaga Nuklir Nasional (BATAN) dalam menahan beban tekanan tinggi dan transfer panas selama proses iradiasi berkas proton, serta rekomendasi parameter iradiasi yang efektifuntuk produksi 18F.Chamber targetÂ cair terse but dibuat sebagai wadah air yang diperkaya dengan 180 yang selanjutnya diiradiasi dengan berkasproton berenergi tinggi untuk produksi 18F. Simulasi computer menggunakan program SRIM juga dilakukan untuk menentukan jangkauan berkas proton berenergi tinggi (sampai dengan 20 MeV) kedalam target air mumi. Impuritas radioaktif yang mungkin dihasilkan dari material penyusun chamber tersebut akibat iradiasiberkas proton juga dibahas berdasarkan hasil studi literatur. Analisis transfer panas juga dilaksanakan oleh karena adanya kekhawatiran terhadap panas yang dihasilkan selama iradiasi target, terutama di dalam ruang target, untuk mendapatkan hasil perhitungan awal terhadap kalor yang dihasilkan sebelum uji coba iradiasi. Perhitungan tersebut dilakukan untuk berbagai arus dan energi berkas proton (masing-masing sampai 30 Âµ dan 20 MeV). Hasil perhitungan dan eksperimen awal menunjukkan bahwa chamber target cair tersebut dapat dihandalkan untuk memproduksi 18F dari target air yang diperkaya 180 dengan mempertahankan tekanan chamber sebesar 3,6 bar jika arus berkas proton dipertahankan sebesar 16 J..lAuntuk semua energi atau jika energi berkas proton dipertahankan sebesar/ dibawah 10 MeV untuk setiap arus. Hasil analisis juga menunjukkan bahwa koefisien transfer panas keseluruhan tergantung pada daya yang diterima oleh target cair terse but.Kata kunci : analisis kehandalan, chamber target cair, produksi 18F, iradiasi proton, siklotron, target air yang diperkaya 18O,koefisien transfer panas.